2001
DOI: 10.1074/jbc.m101213200
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of the Bifunctional 8-Oxoguanine/β-δ Apurinic/Apyrimidinic DNA Repair Activities ofDrosophila Ribosomal Protein S3 into the Human S3 Monofunctional β-Elimination Catalyst through a Single Amino Acid Change

Abstract: The Drosophila S3 ribosomal protein has important roles in both protein translation and DNA repair. In regards to the latter activity, it has been shown that S3 contains vigorous N-glycosylase activity for the removal of 8-oxoguanine residues in DNA that leaves baseless sites in their places. Drosophila S3 also possesses an apurinic/apyrimidinic (AP) lyase activity in which the enzyme catalyzes a ␤-elimination reaction that cleaves phosphodiester bonds 3 and adjacent to an AP lesion in DNA. In certain situatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…coli strain RPC501 was used for overexpressing human GST-S3 [18]. Overnight E. coli cultures bearing human GST-S3 plasmid construct were grown at 37 °C up to A 595 of 0.5 OD and induced with 1 mM Isopropyl-1-thio-β-D-galactopyranoside (IPTG) for 3 h at 27 °C.…”
Section: Overexpression and Purification Of Human Gst-s3mentioning
confidence: 99%
“…coli strain RPC501 was used for overexpressing human GST-S3 [18]. Overnight E. coli cultures bearing human GST-S3 plasmid construct were grown at 37 °C up to A 595 of 0.5 OD and induced with 1 mM Isopropyl-1-thio-β-D-galactopyranoside (IPTG) for 3 h at 27 °C.…”
Section: Overexpression and Purification Of Human Gst-s3mentioning
confidence: 99%
“…After revealing this domain as the major RECQL4 interaction domain responsible for helicase activity inhibition, we studied whether the C-RPS3 is responsible for AP endonuclease activity of human RPS3. This domain was previously reported to have homology with HhH motif of the Escherichia coli AP endonuclease, endonuclease III (24). We assessed the AP endonuclease activity of purified FL-RPS3, N-RPS3, and C-RPS3 on circular double-stranded depurinated substrates using a plasmid nicking assay.…”
Section: Resultsmentioning
confidence: 99%
“…Together, these data confirmed that the N-terminal 1-320 aa of RECQL4 (N-RECQL4) and the C-terminal 94 -244 aa of RPS3 (C-RPS3) are the main interaction domains. Human N-RECQL4 (1-320 aa) is known to have a Sld2 homologous region (9), whereas the C-RPS3 (94 -244 aa) domain has a putative hairpin-helix-hairpin (HhH) motif known for AP endonuclease activity (24).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations